Miltefosine-Lopinavir Combination Therapy Against Leishmania infantum Infection: In vitro and in vivo Approaches - Rebello, Karina M.; Andrade-Neto, Valter V.; Gomes, Claudia Regina B.; de Souza, Marcos Vinícius N.; Branquinha, Marta H.; Santos, André L. S.; Torres-Santos, Eduardo Caio; d'Avila-Levy, Claudia M. (Frontiers in Cellular and Infection Microbiology, 2019)
Concurrently, leishmaniasis and AIDS are global public health issues and the overlap between these diseases adds additional treats to the management of co-infected patients. Lopinavir (LPV) has a well characterized anti-HIV and leishmanicidal action, and to analyze its combined action with miltefosine (MFS) could help to envisage strategies to the management of co-infected patients. Here, we evaluate the interaction between LPV and MFS against Leishmania infantum infection by in vitro and in vivo approaches. The effect of the compounds alone or in association was assessed for 72 h in mouse peritoneal macrophages infected with L. infantum by the determination of the IC50s and FICIs. Subsequently, mice were orally treated twice daily during 5 days with the compounds alone or in association and evaluated after 30 days. The in vitro assays revealed an IC50 of 0.24 µM and 9.89 µM of MFS and LPV, respectively, and an additive effect of the compounds (FICI 1.28). The in vivo assays revealed that LPV alone reduced the parasite load in the spleen and liver by 52% and 40%, respectively. The combined treatment of infected BALB/c mice revealed that the compounds alone required at least two times higher doses than when administered in association to virtually eliminate the parasite. Mice plasma biochemical parameters assessed revealed that the combined therapy did not present any relevant hepatotoxicity. In conclusion, the association of MFS with LPV allowed a reduction in each compound concentration to achieve the same outcome in the treatment of visceral leishmaniasis. Although a pronounced synergistic effect was not evidenced, it does not discard that such combination could be useful in humans co-infected with HIV and Leishmania parasites.